Lipid-lowering and Antiatherosclerotic Effect of NK-104, a Potent 3-Hydroxy-3-methylglutaryl Coenzyme A Reductase Inhibitor, in Watanabe Heritable Hyperlipidemic Rabbits - Suzuki, Hideo; Yamazakis, Hiroyuki; Aoki, Taro; Kojima, Junji; Tamaki, Taro; Sato, Fumiyasu; Kitahara, Masaki; Saito, Yasushi (Arzneimittelforschung, 2000)
NK-104 ((+)-monocalcium bis{(3R,5S,6E)-7-[2-cyclopropyl-4-(4-fluorophenyl)-3-quinolyl]-3,5-dihydroxy-6-heptenoate}, CAS 147526-32-7) an inhibitor of 3-hydroxy-3-metylglutaryl coenzyme A reductase, was administered in drinking water (0.5 mg/kg equivalent) to Watanabe heritable hyperlipidemic (WHHL) rabbits for 26 weeks. It lowered plasma total cholesterol (TC,7-20 %) and triglyceride (TG, 16-39 %) levels throughout the experimental period due to a significant reduction of very low density lipoprotein cholesterol (VLDL-C, 61-62 %, p < 0.05), intermediate density lipoprotein cholesterol (IDL-C, 49-60 %, p < 0.05), VLDL-TG (40-53 %,p=0.06-0.08) and IDL-TG (29-59 %,p=0.06-0.14); low density lipoprotein cholesterol (LDL-C) was not affected. The pattern of the lipoprotein reduction along with a decrease in liver cholesteryl ester (CE, 33.1 %, p < 0.01) suggests an intense reduction of VLDL secretion and a marginal induction of LDL-receptor. Enhanced expression of LDL receptor-related protein (LRP) in the liver was observed at mRNA levels (49.5 % increase, P=0.13), which might play a role in the lipoprotein reduction. Histological analyses of aorta revealed that aortic arch showed the most advanced lesions with larger lesion area (70.0 vs 41.3 %) and much greater CE content (more than 2 fold) with less macrophages than thoracic aorta. NK-104 decreased the surface lesion area at the arch (23.1 %, p=0.054) and reduced the degeneration of media in the thoracic aorta (69.9 % increase in medial smooth muscle cells, p < 0.01). Thus NK-104 preferentially reduced TG-rich lipoproteins (VLDL and IDL) without affecting LDL-C levels and prevented progression of atherosclerosis in WHHL rabbits.
Keywords: Atherosclerosis, experimental; CAS 147526-32-7; HMG-CoA reductase inhibitor; (+)-Monocalcium bis{(3R,5S,6E)-7-[2-cyclopropyl-4-(4-fluorophenyl)-3-quinolyl]-3; 5-dihydroxy-6-heptenoate}; NK-104, hypolipidemic effect, WHHL rabbit